Klausula Baku Pada Perjanjian Berjangka Dan Perlindungan Hukum Bagi Investor Perdagangan Berjangka Komoditi - Namira, Sheila (Cendekia Niaga, 2022)
Legal protection of customers or investors in the world of commodity futures trading needs to be considered. Many victims of the case of "spoofed investment" who suffered losses with a nominal that is not small. By using the normative juridical method, it is hoped that this research can realize justice and legal certainty in the world of futures trading. This study focuses on the standard clauses on futures agreements and consumer legal protection, in this case customers or investors. Law No. 10 of 2011 in conjunction with Law 32 of 1997 concerning Commodity Futures Trading which aims to ensure legal certainty and protect consumers who carry out futures trading transactions. Likewise with Law no. 8 of 1999 concerning Consumer Protection. Both laws have the aim of protecting consumers. Before making a transaction, the customer or investor must meet the requirements for customer acceptance, one of which is by signing agreements. The agreement is in the form of a standard contract. The contents of the agreement are made by Bappebti. Therefore, the contents of the agreement have taken into account aspects of consumer protection. As a form of self-protection, customers can find out about brokerage companies through the web www.Bappebti.go.id or come directly to the Bappebti Building Floors 3 â€“ 7 on Jl. Kramat Raya No. 172 Jakarta or CoFTRA's call center at (021) 31924744 and SMS center at 0811-1109-901. Bappebti also provides tips on protecting customers or investors with the â€œ7Psâ€. If a problem occurs in the future, the customer or investor can submit a complaint either to the division that serves complaints at the brokerage firm, futures association, and Bappebti. If the problem has not been resolved by deliberation, it will be resolved through the District Court or Commodity Futures Trading Arbitration.